Jälkitavujen h:n variaation kehityksestä Tornionjokilaaksossa - Vaattovaara, Johanna (Virittäjä, 2002)
The use of h in non-initial syllabes in the Tornio valley (englanti) 4/2002 (106) The use of h in non-initial syllabes in the Tornio valley The survival of the h in non-initial syllables (e.g. lhethn, saunahan) is a relic of phonological history that is no longer heard in most of the present dialects of Finnish. Its present geographical distribution is limited largely to Ostrobothnian and Northern Finnish dialects, although even in these it is generally in decline. However, in one area, the Tornio Valley, it is thriving and is even on the increase. The h has been affected by many phonological changes in the Tornio dialects and is no longer heard in its original intervocalic position. Instead, it either 1) follows an apocopated vowel, e.g. lhethn, saunhaan, 2) is metathetically shifted to precede a voiced consonant, e.g. sauhnaan, kauhniit, or 3) is assimilated to the preceding consonant so that it resembles a form caused by primary gemination (e.g. satheita > satteita) or secondary gemination (e.g. toisheen > toisseen), or a Standard Finnish form (e.g. kauphaan > kauppaan). Forms in which the /h/ has been lost (e.g. taloon, sateita) are used only slightly more frequently in the dialect by those born in the 1980s than those born at the end of the nineteenth century. From a language-internal perspective, this is explained by the fact that primary gemination has become phonemic in the dialect, which thus has somewhat shorter main-stress syllables: satteeseen instead of sateeseen, and venneit instead of veneit, etc. With the /h/ remaining (e.g. satheeseen, venheit), the quantitative relations of the syllables are the same as in primary geminated forms (CVC-), whereas the loss of /h/ would bring about a shift to the CV form: sateeseen, veneit. The use of /h/ in non-initial syllables is nevertheless undergoing change in the Tornio dialects too. This is logical from a language-internal perspective. The syncope affecting vowels preceding /h/ has created a considerable number of C+/h/ clusters in the dialect that are contrary to Finnish phonotactics: */ph th kh sh hh vh jh mh/ (e.g. kauphaan, satheen, etc.). The speech community is now moving away from these syncopic variants and replacing them mainly with a metathetical variant in linguistic contexts in which the phonotactic preconditions exist for metathetical change. In environments (mainly unvoiced) lacking the preconditions for metathetical change, syncope is normally replaced by assimilated forms (e.g. talhoon > talloon, toisheen > toisseen). Forms without the /h/ are most commonly used when the replacement of a phonotactically unacceptable cluster with the phonological change mentioned above would otherwise give rise to another unacceptable cluster, as in the following case: tosijhaan > tosihhaan > tosiaan. The present use of /h/ in the Pello district can be considered a consequence of the prevailing conspiracy to bring about phonological change and return the dialect to its former phonotactic state. Language-internal change will naturally not occur unless the language-external world supports the change. The underlying reason for the use of /h/ in the Tornio Valley is that the speech community has no need for the h-less forms of Standard Finnish and wishes to use its own dialectal form not found elsewhere. This is the metathetical /h/ functioning as a linguistic identity symbol for the people of the Tornio Valley region. JOHANNA VAATTOVAARA